The Role of Antioxidant Structure in Mitigating Oxidation in Ti3C2Tx and Ti2CTx MXenes. Issue 20 (12th June 2022) - Zhao, Xiaofei; Cao, Huaixuan; Coleman, Bryan J.; Tan, Zeyi; Echols, Ian J.; Pentzer, Emily B.; Lutkenhaus, Jodie L.; Radovic, Miladin; Green, Micah J.
Abstract: The oxidation of 2D MXenes jeopardizes their shelf life, both in colloidal dispersions and in functional devices. Certain compounds have been shown to effectively mitigate oxidation of MXenes (such as sodium L‐ascorbate, ascorbic acid, and polyanions), but the nature of interaction between these antioxidants and MXene remains unknown, which impedes the future selection and design of improved protection. This work systematically examines the interactions between three classes of organic antioxidant candidates, α‐hydroxy acids, polycarboxylic acids, and phenols with Ti n +1 C n T x MXenes, specifically Ti3 C2 T x and Ti2 CT x . Interestingly, while some antioxidants provide no protection for the MXenes, and some antioxidants even accelerate their degradation, three antioxidants (e.g., citric acid, tartaric acid, and oxalic acid) protect the MXene nanosheets exceptionally well, showing minimum MXene degradation after the 14‐day storage period. Analysis of the antioxidants' molecular structure and efficacy suggests that chelation interactions with the transition metal atoms of the nanosheets play a key role in effective protection of MXenes from oxidation. Abstract : MXenes are an exciting class of 2D nanomaterials, but they are prone to oxidize and degrade, particularly in aqueous dispersions. This work systematically examines the interactions between antioxidants and common MXenes (Ti3 C2 T x and Ti2 CT x ) and shows how the molecular structure of the antioxidant allows for the nanomaterial to be protected.